2023
DOI: 10.1177/10406387231151663
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of diaphragm meat juice and muscle swab samples to spleen and spleen swab samples for the detection of African swine fever viral nucleic acid

Abstract: Use of meat juice and muscle swabs at slaughterhouses may provide an easy-to-collect sample for African swine fever (ASF) surveillance. Meat juice has been experimentally shown to be a reliable sample for the detection of ASF virus (ASFV). We compared the detection of ASFV nucleic acid from diaphragm meat juice, diaphragm muscle swab, spleen, and spleen swabs from pigs with signs of ASFV infection at slaughterhouses around Kampala, Uganda. Pigs with ≥ 2 clinical or pathology signs at the time of slaughter had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This is because of the large number of Kupffer cells available as ASFV target cells (Blome et al, 2020). The PCR band for the spleen was thick (Okwasiimire et al, 2023). This is because the spleen has abundant macrophages and monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…This is because of the large number of Kupffer cells available as ASFV target cells (Blome et al, 2020). The PCR band for the spleen was thick (Okwasiimire et al, 2023). This is because the spleen has abundant macrophages and monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Pigs that are infected but not yet showing clinical signs and are active may be shedding ASF in oral fluid therefore applying this method at the first sign of ASF in a herd could assist rapid confirmation [ 41 , 42 , 43 ]. Information exists on other samples that may be required for trade purposes and surveillance and can easily be obtained, such as meat and meat exudate [ 44 , 45 , 46 , 47 , 48 ]. The concurrence between positive spleen and muscle samples in the Ugandan study [ 46 ] indicated that viraemic pigs were presented for slaughter, which is often the case during ASF outbreaks, when farmers rapidly sell their pigs to limit financial losses, as has been reported previously [ 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Challenges For Early Detection and Confirmation Of Asfmentioning
confidence: 99%
“…Information exists on other samples that may be required for trade purposes and surveillance and can easily be obtained, such as meat and meat exudate [ 44 , 45 , 46 , 47 , 48 ]. The concurrence between positive spleen and muscle samples in the Ugandan study [ 46 ] indicated that viraemic pigs were presented for slaughter, which is often the case during ASF outbreaks, when farmers rapidly sell their pigs to limit financial losses, as has been reported previously [ 49 , 50 , 51 , 52 , 53 , 54 ]. This practice poses a risk for the spread of ASF but does offer opportunities for ASF surveillance and earlier diagnosis at points of sale.…”
Section: Challenges For Early Detection and Confirmation Of Asfmentioning
confidence: 99%